(untitled) (Jalalabad Medical Journal, 2026)
Neonatal hyperbilirubinaemia is one of the commonest problems in the early days of life. Hyperbilirubinaemia occur in 80% of preterm and 60% of term infants in the first week of life. It is a significant cause of morbidity among neonates worldwide. So, the study aims to determine the risk factors of neonatal hyperbilirubinaemia and its outcome in a tertiary care setting. This cross-sectional type of descriptive study was conducted in the neonatal unit of the paediatrics department of Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, from September 2018 to February 2019. A total of 100 clinically jaundiced neonates were enrolled in the study. Data were collected by using a structured questionnaire. Study results revealed that 63% were male, and 61% babies were 1-3 days of age, with the majority (52%) had a birth weight ≥2500 grams. The majority (61%) of the patients were >37 weeks gestational age, and most (87%) of them belonged to middle socioeconomic conditions. Fifty-four percent of babies had the features of sepsis. Among the neonates, 12% had serum bilirubin levels of 20 mg/dl or more and 93% of patients were treated with phototherapy. Exchange transfusion was conducted in 8% of cases. Fifty-four percent of neonates were discharged within 5 days of admission. Seven percent (7%) of patients were discharged on request and 93% were discharged with advice after recovery. In conclusion, the present study found that 1-3 days of male babies with a birth weight ≥2500 grams and a gestational age >37 weeks having features of sepsis developed neonatal hyperbilirubinaemia. All of the neonates admitted in the hospital were improved at discharge. Jalalabad Med J 2025; 22 (2): 72-77